Genistein suppresses tumor necrosis factor α-induced inflammation via modulating reactive oxygen species/Akt/nuclear factor ΚB and adenosine monophosphate-activated protein kinase signal pathways in human synoviocyte MH7A cells - Li J; Li J; Yue Y; Hu Y; Cheng W; Liu R; Pan X; Zhang P (Dove Medical Press, 2014)
Jinchao Li,1,* Jun Li,2,* Ye Yue,1 Yiping Hu,1 Wenxiang Cheng,1 Ruoxi Liu,3 Xiaohua Pan,4 Peng Zhang1 1Center for Translational Medicine Research and Development, Shenzhen Institute of Advanced Technology, Chinese Academy of Science, Shenzhen, 2Emergency Surgery Department, Shaanxi Provincial People’s Hospital, Xi’an, 3Department of Orthopedics, Shandong University of Traditional Chinese Medicine, Jinan, 4Department of Orthopedics, Second Clinical Medical College, Jinan University, Shenzhen, People’ Republic of China *These authors contributed equally to this work Aims: Genistein, an isoflavone derivative found in soy, is known as a promising treatment for rheumatoid arthritis (RA). However, the detailed molecular mechanism of genistein in suppression of proinflammatory cytokine production remains ambiguous. The aim of this work was to evaluate the signal pathway by which genistein modulates inflammatory cytokine expression. Materials and methods: MH7A cells were stimulated with tumor necrosis factor (TNF)-α and incubated with genistein, and interleukin (IL)-1β, IL-6, and IL-8 production was measured by enzyme-linked immunosorbent assay. Nuclear translocation of nuclear factor (NF)- ΚB was measured by a confocal fluorescence microscopy. The intracellular accumulation of reactive oxygen species (ROS) was monitored using the fluorescent probe 5-6-chloromethyl-2´,7´-dichlorodihydrofluorescein diacetate. Signal-transduction protein expression was measured by Western blot. Results: Genistein decreased the secretion of IL-1β, IL-6, and IL-8 from TNF-α-stimulated MH7A cells in a dose-dependent manner. Genistein prevented TNF-α -induced NF-ΚB translocation as well as phosphorylation of IΚB kinase-α/β and IΚBα, and also suppressed TNF-α-induced AMPK inhibition. The production of IL-1β, IL-6, and IL-8 induced by TNF-α was decreased by the phosphatidylinositol-3 kinase inhibitor LY294002, suggesting that inhibition of Akt activation might inhibit IL-1β, IL-6, and IL-8 production induced by TNF-α. In addition, we also found that pretreatment with the adenosine monophosphate-activated protein kinase (AMPK) agonist 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside obviously inhibited TNF-α-induced proinflammatory cytokine production. These observations suggest that the inhibitory effect of genistein on TNF-α-induced proinflammatory cytokine production is dependent on AMPK activation. Conclusion: These findings indicate that genistein suppressed TNF-α-induced inflammation by inhibiting the ROS/Akt/NF-ΚB pathway and promoting AMPK activation in MH7A cells. Keywords: genistein, rheumatoid arthritis, cytokine, signal transduction, inflammation